Platelet Counts and Liver Enzymes after Bariatric Surgery - Hans-Erik Johansson; Arvo Haenni; Björn Zethelius (Journal of Obesity)
Background. Obesity is characterized by liver steatosis, chronic inflammation, and increased liver enzymes, that is, gamma-glutamyltransferase (GGT) and alanine aminotransferase (ALT), markers for nonalcoholic fatty liver disease (NAFLD) and liver fat content. Increased platelet counts (PCs) are associated with inflammatory conditions and are a valuable biomarker of the degree of fibrosis in NAFLD. We investigated alterations in PC, GGT, and ALT after biliopancreatic diversion with duodenal switch (BPD-DS) and Roux-en-Y gastric bypass (RYGBP). Methods. Ten morbidly obese patients (body mass index, BMI: 53.5±3.8 kg/m2) who underwent BPD-DS were evaluated preoperatively (baseline) and 1 year (1st followup) and 3 years (2nd followup) after surgery and compared with 21 morbidly obese patients (BMI: 42.3±5.2 kg/m2) who underwent RYGBP. Results. Over the 3 years of followup, changes in BPD-DS and RYGBP patients (BPD-DS/RYGBP) were as follows: BMI (−44%/−24%), GGT (−63%/−52%), and ALT (−48%/−62%). PC decreased (−21%) statistically significantly only in BPD-DS patients. Conclusions. Morbidly obese patients treated by RYGBP or BPD-DS show sustained reductions in BMI, ALT, and GGT. The decrease in PC and liver enzymes after BPD-DS may reflect a more pronounced decrease of liver-fat-content-related inflammation and, as a result, a lowered secondary thrombocytosis.